2013
DOI: 10.1039/c2sc21263c
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing thermal fluctuations for purposeful activities: the manipulation of single micro-swimmers by adaptive photon nudging

Abstract: A simple scheme is presented for remotely maneuvering individual microscopic swimmers by means of ondemand photo-induced actuation, where a laser gently and intermittently pushed the swimmer along its body axis (photon nudging) through a combination of radiation-pressure force and photophoretic pull.The proposed strategy utilized rotational random walks to reorient the micro-swimmer and turned on its propulsion only when the swimmer was aligned with the target location (adaptive control). A Langevin-type equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
219
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(231 citation statements)
references
References 45 publications
11
219
1
Order By: Relevance
“…(16). On that level, the rate of change of the system entropy is given aṡ S(t) = −d/dt ln ρ(χ(t), t)σ , with .…”
Section: Entropy Production and Workmentioning
confidence: 99%
See 2 more Smart Citations
“…(16). On that level, the rate of change of the system entropy is given aṡ S(t) = −d/dt ln ρ(χ(t), t)σ , with .…”
Section: Entropy Production and Workmentioning
confidence: 99%
“…In the "mean-field" limit, we can thus consider the feedback force as a conventional time-dependent force entering the "mean field" version of Eq. (16), that is, γχ(t) = −V (χ) + F fc (z(t − τ D )) + 2γk B T ξ(t) . (19) From Eq.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically taking the form of bifunctional Janus particles [3], such colloidal swimmers are driven by gradients of concentration and temperature that result from chemical reactions [1,4]. Several examples of light-activated colloidal swimmers have been reported whose motions are driven by thermophoresis [5][6][7][8][9]. This mode of motion recently has been analyzed theoretically [10].…”
Section: Introductionmentioning
confidence: 99%
“…With experiments and simulations, it has been demonstrated that even in the presence of rotational diffusion, autonomous microswimmers can perform a directed motion when moving along planar or patterned walls, funnels, channels, or chemical gradients [9][10][11][12][13]. Alternatively, steering of active particles can also be achieved using feedback loops which control the particle propulsion depending on its position and orientation [14,15]. Employing optical and thermophoretic forces (photon nudging), it has been shown that high spatial localization of active particles can be achieved [15,16].…”
Section: Introductionmentioning
confidence: 99%